The Effect Of Net Interest Margin, Operating Cost of Operating Income, And Loan To Deposit Ratio On Return On Asset At PT Bank Commonwealth Period 2012-2022 - Ina Zakiah, Pelni Shifa Dewi; Listri Herlina (DINASTI RESEARCH, 2024)
Profitability is a ratio to assess the company's ability to seek profit. This ratio also provides a measure of the effectiveness of a company's management. Profitability at PT Bank Commonwealth for the period 2012-2022 decrease. This study aims to determine the effect of Net Interest Margin, Operating Cost of Operating Income, Loan to Deposit Ratio on Return On Asset for the period 2012-2022.This research uses quantitative methods with a descriptive verification approach. The data source used is secondary data with documentation data collection in the form of annual financial reports and purposive sampling techniques.The results showed that the average of -0.05% was categorized as unhealthy and was below Bank Indonesia's provisions for a healthy Return On Asset category of 1.5%. Net Interest Margin average of 4.88% which is categorized as unhealthy because it is below the provisions of Bank Indonesia for the healthy category of 6%. Operating Cost of Operating Income average of 100.9% which is categorized as unhealthy because it is above the provisions of Bank Indonesia for the healthy 89%. The average Loan to Deposit Ratio is 87.9 which is categorized as healthy, however, the Loan to Deposit Ratio at the end of the research period in 2022 is 76.61% and is below the bank's health which is 80%-110%. Partially Net Interest Margin has a significant effect on Return On Asset with a contribution of 58.5%. Operating Cost of Operating Income has a significant effect on Return On Asset with a contribution of 14.3%. Loan to Deposit Ratio has no significant effect on Return On Asset with a contribution of 0.6%. Together (simultaneously) Net Interest Margin, Operating Cost of Operating Income, Loan to Deposit Ratio have a significant effect on Return On Asset with a contribution of 64.9% at PT Bank Commonwealth Period 2012-2022.